Modernization and Renewal Islamic Education in the Era of Society 5.0: A Systematic Review - Syafaruddin, Baso (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
Currently, the development of information technology has reached all levels of society, including Islamic religious education. Industrial progress has made it necessary for society to be capable of addressing all the challenges that exist today. The effects of both 5.0 have a significant influence on human life and educational institutions. To anticipate the negative impacts of advances in science and technology, as well as the rapid pace of modernization, individuals must immediately become aware of and strengthen their religious knowledge within themselves. This study employs a systematic review research approach, scrutinizing literature-based data sources about the modernization of Islamic religious education in the Era of Society 5.0. We hope that moral education will cultivate a morally advanced generation, acting as a filter against foreign cultural values that contradict Islamic teachings and Indonesian culture. Information technology development is currently affecting all areas of social life, including education. We need three literacies in the Era of Society 5.0: data literacy, human literacy, and technological literacy. Learning in the era of revolution Revolution 4.0 can implement hybrid/blended learning and case-based learning. Education in the era of Society 5.0 enables students to engage in learning activities alongside robots, designed to supplant the role of educators. This article examines the modernization and renewal of Islamic religious education in the era of society 5.0. In this way, education actors and stakeholders can understand the importance of technology in Islamic education in the era of Society 5.0.